(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Studies have shown that cows from the established families of the Red Desert breed have high milk production potential. Creating breeding groups of high-yielding cows and their widespread use in the process of breed improvement plays an important role in increasing milk production volumes and raising pedigree cattle with high hereditary potential in terms of productivity.